PEMAKNAAN BATIK SEBAGAI WARISAN BUDAYA TAKBENDA - Zahir Widadi (LPPM Universitas Pekalongan, 2019)
This research aims to improve the knowledge and understanding of the intangible culture heritage because many people do not understand the meaning of the confirmation of Indonesian batik as a intangible cultural heritage by UNESCO. This research uses qualitative research methods with descriptive format. The intangible cultural heritage means the practices, representations, expressions, knowledge, skills – as well as the instruments, objects, artefacts and cultural spaces associated therewith – that communities, groups and, in some cases, individuals recognize as part of their cultural heritage. The intangible culture heritage comprises of domains oral traditions and expressions, including language as a vehicle of the Intangible cultural heritage, performing arts, social practices, rituals and festive events, knowledge and practices concerning Nature and the universe, and traditional craftsmanship. Domains of the intangible cultural heritage in accordance with Indonesian batik consist of the domain oral traditions and expressions, including language as a vehicle of the intangible Cultural heritage, social practices, rituals and festive events, and traditional craftsmanship.